2022
DOI: 10.3390/microorganisms10030627
|View full text |Cite
|
Sign up to set email alerts
|

Epitheliocystis in Greater Amberjack: Evidence of a Novel Causative Agent, Pathology, Immune Response and Epidemiological Findings

Abstract: Epitheliocystis is a fish gill disease caused by a broad range of intracellular bacteria infecting freshwater and marine fish worldwide. Here we report the occurrence and progression of epitheliocystis in greater amberjack reared in Crete (Greece). The disease appears to be caused mainly by a novel Betaproteobacteria belonging to the Candidatus Ichthyocystis genus with a second agent genetically similar to Ca. Parilichlamydia carangidicola coinfecting the gills in some cases. After a first detection of the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 84 publications
(107 reference statements)
1
4
0
Order By: Relevance
“…4 ). This is in compliance with previous phylogenies using 16S rRNA sequences (Contador et al 2016 ; Seth-Smith et al 2016 ; Cascarano and Katharios 2022 ; Cascarano et al 2022 ). Consequently, it is reasonable to believe that all taxa of this clade share the same common ancestor of Cand .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…4 ). This is in compliance with previous phylogenies using 16S rRNA sequences (Contador et al 2016 ; Seth-Smith et al 2016 ; Cascarano and Katharios 2022 ; Cascarano et al 2022 ). Consequently, it is reasonable to believe that all taxa of this clade share the same common ancestor of Cand .…”
Section: Discussionsupporting
confidence: 91%
“…Ichtyocystis hellenicum). Recent studies have identified new agents of this genus associated with epitheliocystis in reared greater amberjack ( Seriola dumerili ), wild-caught Pacific herring ( Clupea pallasii ) and Pacific mackerel ( Scomber japonicus ) (Cascarano et al 2022 ), as well as from pompano ( Trachinotus ovatus ) (Cascarano and Katharios 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations